Educationally valuable activities and learning experiences outside the educational center - Molina Ruiz, Enriqueta (2014)
This is a research (Molina, 2005) that approached the subject of community contribution in students formation. Clearly, we are referring to the study of exterior resources outside the school such as parks and public gardens, themain interest is to know the didactic-pedagogic capacity of these places and the way they can be used. Another interest is to obtain information to direct the organization of educational experiences in such contexts, we should know the elements that, coordinated properly, should make possible the accomplishment of formative experiences. As our contribution we share the results about “activities”; we consider these activities are a fundamental element for the application of educational programs. The presentation of a large variety of suggestions about curricular activities carried out in parks and public gardens, reveals the recognition of the teachers of the formative capacity ofsuch means.